Message from HIBIBI 2014 chairs - Naji, Gada; Zeng, Jaia; Kaya, Mehmet; Gao, Shang (Institute of Electrical and Electronics Engineers Inc., 2014)
[Abstract Not Available]
2014 IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining, ASONAM 2014 -- 17 August 2014 through 20 August 2014 -- Beijing -- 108564